On positive solutions of fractional differential equations with change of sign. (28th March 2019) - Wang, Fanglei; Zhang, Li; Ru, Yuanfang; Liu, Ronghua
Abstract : We study the existence and uniqueness of positive solutions of fractional differential equations with change of sign D 0 + α ( u ′ ′ ( t ) ) = h ( t ) f ( u ( t ) ), 0 < t < 1, u ( 0 ) = u ( 1 ) = 0, u ′ ′ ( 0 ) = u ′ ′ ( 1 ) = 0, where 1 < α ≤ 2, h : [ 0, 1 ] → R is continuous and does not vanish identically on any subinterval of [0, 1].